Controllable Enhancement of Evanescent and Transmitted Waves by a Plasma Sphere - Shi, Wenxuan; Yuan, Bin; Mao, Junfa (Frontiers in Physics, 2022)
In this study, we present that the plasma sphere can focus and enhance the evanescent and transmitted wave. Electromagnetic waves propagating in plasma sphere with positive and negative permittivity, which lead to enhance transmitted and evanescent wave, are analyzed. The intensity of focus beam can be hundreds of times stronger than the incident wave. The enhancements effect is associated with plasma frequency, collision frequency and incident wave frequency. The results illustrate that the electromagnetic wave can be focused, reflected, and oscillated by controlling the electromagnetic parameters of the plasma sphere. With strong field enhancement available, it can be possible to use in microwave power amplifiers, plasma antenna, etc.